2016
DOI: 10.1513/annalsats.201603-156oc
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Intensity-modulated Radiation Therapy for Older Patients with Stage III Lung Cancer

Abstract: Rationale: In the treatment of stage III non-small cell lung cancer (NSCLC), three-dimensional conformal radiotherapy (3D-RT) is the standard method for radiation delivery; however, intensitymodulated radiotherapy (IMRT) has been rapidly adopted. These two modalities may lead to similar survival, warranting a closer scrutiny of the costs involved.Objectives: The purpose of this study is to compare radiotherapyrelated and total costs of older patients with NSCLC treated with 3D-RT versus IMRT. Measurements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It is possible that using the CPI for inflation adjustment may have overinflated earlier years of data, biasing our analysis toward the null . However, we felt justified using the CPI given that the CPI has precedent in similar radiotherapy-related spending analyses in the literature . Furthermore, spending results were consistent even when using an alternative inflation index that is not thought to overinflate earlier years of cost data.…”
Section: Discussionmentioning
confidence: 86%
“…It is possible that using the CPI for inflation adjustment may have overinflated earlier years of data, biasing our analysis toward the null . However, we felt justified using the CPI given that the CPI has precedent in similar radiotherapy-related spending analyses in the literature . Furthermore, spending results were consistent even when using an alternative inflation index that is not thought to overinflate earlier years of cost data.…”
Section: Discussionmentioning
confidence: 86%
“…Although single-center retrospective studies found promising results with IMRT despite its use for more advanced disease, population-based retrospective studies showed mixed results. Studies using the SEER database did not show a clear benefit in OS or reduction in pulmonary or esophageal toxicity for IMRT compared to 3DCRT (51)(52)(53)(54). Importantly, toxicity data was based on Medicare claims, which does not provide information on toxicity grade.…”
Section: Retrospective Clinical Studiesmentioning
confidence: 99%
“…Although IMRT is used routinely for locally advanced NSCLC, widespread use is limited because of a lack of highquality evidence establishing superiority and the requirement for more advanced delivery systems and dose calculation algorithms. Using data from the SEER registry linked to Medicare claims, Kale et al estimated that RT-related costs were $6,850 higher per patient for IMRT versus 3DCRT (54).…”
Section: Implementation Challengesmentioning
confidence: 99%
“…6 This is probably because of higher costs incurred per patient when using IMRT for lung cancer, as shown in another report from the Surveillance, Epidemiology, and End Results registry-Medicare. 26 IMRT also requires highly trained staff using more advance planning systems, complex dose calculation algorithms and more advanced radiotherapy delivery systems with robust image-guidance. 4 However, in our high-volume centre with good IMRT planning experience, IMRT was used when necessary for adequately and safely treating the PTV, whilst satisfying the dose constraints for organs at risk.…”
Section: Shrimali Et Almentioning
confidence: 99%